Cell-derived Secretome for the Treatment of Renal Disease - Michael W. Kim; In Kap Ko; Anthony Atala; James J. Yoo (Korean Society of Pediatric Nephrology, 2019)
Kidney disease is a major global health issue. Hemodialysis and kidney transplantation have been used in the clinic to treat renal failure. However, the dialysis is not an effective long-term option, as it is unable to replace complete renal functions. Kidney transplantation is the only permanent treatment for end-stage renal disease (ESRD), but a shortage of implantable kidney tissues limits the therapeutic availability. As such, there is a dire need to come up with a solution that provides renal functions as an alternative to the current standards. Recent advances in cell-based therapy have offered new therapeutic options for the treatment of damaged kidney tissues. Particularly, cell secretome therapy utilizing bioactive compounds released from therapeutic cells holds significant beneficial effects on the kidneys. This review will describe the reno-therapeutic effects of secretome components derived from various types of cells and discuss the development of efficient delivery methods to improve the therapeutic outcomes.